Exploring the impact of the Genre-Based Approach on Academic Writing Proficiency - Abdul Rahman R; Chairil Anwar Korompot; Chaerul Fadlan Saud; Yusran; Badriah (Universitas Sulawesi Barat, 2025)
This research presents a comprehensive exploration of the implementation and potential impact of the Genre-Based Approach (GBA) on academic writing proficiency among English Language Education (EFL) students at Universitas Tomakaka, Indonesia. Utilizing a case study methodology, the report examines the theoretical foundations of GBA, its pedagogical stages, and its alignment with the specific needs of the Indonesian English as a Foreign Language (EFL) context. Findings suggest that GBA, rooted in Systemic Functional Linguistics (SFL), can significantly address common challenges in academic writing, such as limited vocabulary and rhetorical structures. However, its successful implementation is highly dependent on enhancing instructor expertise and careful curriculum integration. The report concludes with practical recommendations for the integration of GBA at Universitas Tomakaka and identifies further research directions to enrich the understanding of the effectiveness of GBA in the specific context of a BBA university. The report implicitly highlights the complex interrelationships between pedagogical theories, unique institutional contexts, and chosen research methodologies. By clearly identifying the “what” (GBA), “where” (Tomakaka University), and “how” (case study methodology), the report immediately establishes its scope and practical relevance. This concise synthesis shows how theoretical pedagogical approaches can be tested for real-world application in a specific educational setting, underscoring the applied nature of the proposed research.